Experimental research on droplets releasing characteristics of the bubble bursting behavior at a free surface with an aerosol. (August 2022) - Yu, Xiang; Gu, Haifeng; Yin, Weikai; Sun, Qingyang; Zhou, Yanmin
Highlights: The number and speed of film droplets increase, and the size decrease with the cap film thickness. As the liquid temperature increases, the number of droplets slightly increases, the size increases, and the speed decreases. Both Rayleigh and Γ distribution can describe the normalized size distribution of film droplets in distilled water and aerosol suspension. Under low liquid temperature, the addition of TiO2 may increase the number of film droplets and reverse in high temperature. Abstract: Bubble burst phenomena exist widely in industrial and environmental processes and exert a subtle influence. Bubbles may be produced by gas injection or boiling and will burst after floating at the free surface of the pool for a while. The produced film droplets and jet droplets will entrain the liquid substance into the gas, especially in reactor accidents. When aerosols retain in the pool, radioactive aerosol-laden droplets may exert a long-lasting source term that needs to be addressed to evaluate this source more precisely. The bubble bursting and film droplets producing behavior at the free surface under different conditions are investigated by visualization. Image processing software is applied to measure the size, number, and speed of film droplets. By comparing the bubble cap film thickness and the film roll-up speed to the number of droplets under different liquid temperatures both in distilled water and aerosol suspension, we show that the increase of the cap film thickness (decrease of the bubble lifetime) attributes to the decline of the number and average speed of film droplets and the increase of average size. The normalized droplet speed obeys the multimodal distribution. The normalized droplet size distribution obeys the gamma distribution and the Rayleigh distribution. The goodness of fit for gamma distribution of distilled water can reach 88%, and aerosol suspension is 70%. The increase of the liquid temperature will slightly increase the number and average size of film droplets but decrease the average speed for distilled water and aerosol suspension. Under low temperature, adding TiO2 aerosol may increase the number of film droplets; under high temperature, the aerosol may reduce the number of droplets.